Empathy, Challenge, and Psychophysiological Activation in Therapist–Client Interaction - Voutilainen, Liisa; Henttonen, Pentti; Kahri, Mikko; Ravaja, Niklas; Sams, Mikko; Peräkylä, Anssi (Frontiers in Psychology, 2018)
Two central dimensions in psychotherapeutic work are a therapist’s empathy with clients and challenging their judgments. We investigated how they influence psychophysiological responses in the participants. Data were from psychodynamic therapy sessions, 24 sessions from 5 dyads, from which 694 therapist’s interventions were coded. Heart rate and electrodermal activity (EDA) of the participants were used to index emotional arousal. Facial muscle activity (electromyography) was used to index positive and negative emotional facial expressions. Electrophysiological data were analyzed in two time frames: (a) during the therapists’ interventions and (b) across the whole psychotherapy session. Both empathy and challenge had an effect on psychophysiological responses in the participants. Therapists’ empathy decreased clients’ and increased their own electrodermal activity across the session. Therapists’ challenge increased their own EDA in response to the interventions, but not across the sessions. Clients, on the other hand, did not respond to challenges during interventions, but challenges tended to increase EDA across a session. Furthermore, there was an interaction effect between empathy and challenge. Heart rate decreased and positive facial expressions increased in sessions where empathy and challenge were coupled, i.e., the amount of both empathy and challenge was either high or low. This suggests that these two variables work together. The results highlight the therapeutic functions and interrelation of empathy and challenge, and in line with the dyadic system theory by Beebe and Lachmann (2002), the systemic linkage between interactional expression and individual regulation of emotion.